Interaction of blood plasma with antifouling surfaces - Rodriguez Emmenegger, C; Brynda, E; Riedel, T; Sedlakova, Z; Houska, M; Alles, A Bologna (Langmuir, 2009)
Nonspecific adsorption of proteins is a crucial problem in the detection of analytes in complex biological media by affinity sensors operating with label-free detection. We modified the gold surface of surface plasmon resonance (SPR) sensors with three types of promising antifouling coatings: self-assembled monolayers (SAM)s of alkanethiolates terminated with diethylene glycol and carboxylic groups, poly(ethylene glycol) (PEG) grafted onto the SAMs, and zwitterionic polymer brushes of poly(carboxybetaine methacrylate), poly(sulfobetaine methacrylate), and poly(phosphorylcholine methacrylate). Using SPR, we compared the efficacy of the coatings to reduce nonspecific adsorption from human blood plasma and from single-protein solutions of human serum albumin, immunoglobulin G, fibrinogen, and lysozyme. There was no direct relationship between values of water contact angles and plasma deposition on the coated surfaces. A rather high plasma deposition on SAMs was decreased by grafting PEG chains. Fouling on PEG was observed only from plasma fractions containing proteins with molecular mass higher than 350 000 Da. The adsorption kinetics from plasma collected from different healthy donors differed. Poly(carboxybetaine methacrylate) completely prevented the deposition from plasma, but the other more hydrophilic zwitterionic polymers prevented single-protein adsorption but did not prevent plasma deposition. The results suggest that neither wettability nor adsorption of the main plasma proteins was the main indicator of deposition from blood plasma.
Keywords: Adsorption; Gold; Humans; biologické modely; zlato; adsorpce; krevní plazma; Plasma; Surface Properties; Models, Biological; povrchové vlastnosti; lidé